(untitled) (e-Journal of Linguistics, 2026)
This research aims to analyze the construction of "hear" verb phrases in Indonesian syntactically and semantically. This research uses a qualitative descriptive approach with data sourced from a Leipzeg corpus of spoken and written texts. The results show that the construction of the verb phrase "hear" has several structural patterns and different meanings. The structure patterns include: S-P-O: Subject - Predicate - Object; S-P-O-PP: Subject - Predicate – Object - Preposition - Phrase; and S-P-Clause: Subject - Predicate - Clause. The meaning of the construction of the verb phrase "hear" also varies, including: (1) to hear the sound, i.e. this construction is used to state that the subject perceives the sound through his/her hearing; (2) to hear the news; i.e. this construction is used to state that the subject receives information through his/her hearing; (3) to hear explanation; i.e. this construction is used to state that the subject receives explanation through his/her hearing. This study also shows that the construction of the verb phrase "hear" can be modified with various phrases, such as time phrases, place phrases, and manner phrases. These modifications can change the meaning and the function of the construction of the verb phrase “hear” in the sentence.